PENGARUH DESENTRALISASI, KETIDAKPASTIAN LINGKUNGAN DAN PENGENDALIAN AKUNTANSI TERHADAP KINERJA MANAJERIAL PADA PEMERINTAH KOTA BAU-BAU DAN KABUPATEN BUTON - Muntu Abdullah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
The purpose of this research is knowing the effect of decentralization, environment uncertainty and accounting control to the managerial performance. Approach which is used to test the research hypothesis is by using the statistical test. The method of data collection use survey method through questionnaire that allotted to 300 people of low and middle level manager in Governmental Office of Bau-Bau City and Buton Regency. However, the valid questionnaires to be used are 212. Independent variables in this research are decentralization (X1), environment uncertainty (X2), and accounting control (X3). While dependent variable is managerial performance (Y). Regression coefficient of X1 variable = 0.262, X2 variable = -0.260, and X3 variable, regression coefficient = 0.307. Partial determination coefficient of X1 variable is 0.41 (41%), for X2 variable, partial determination coefficient = 0.30 (30%), and X3 variable, partial determination coefficient = 0.38 (38%). The research result indicated that the coefficient of simultaneous correlation is 0.783 (78.3%), it meant by together variable of X1, X2 and X3 are strongest correlation with managerial performance variable (Y). The coefficient of simultaneous determination is 0.612 (61.2%) it meant that by together variable of X1, X2 and X3 can explaine variance of the fluctuation of managerial performance variable (Y) is 61.2% and the remain is 38.8% determined by other factors. The result of F-test, indicated that the result of F-Value is (109.563) > from F-table (2.65) so hypothesis which state that “Variable of X1, X2, and X3 which estimated simultaneously have affected managerial performance variable (Y), indicated that the first hypothesis has been proved or accepted, it is according to probability or significant on 0.000 (0.0 %) which be under 5 % of the tolerance limit. The result of T test, for decentralization variable (X1) t-Value is 7.755 > t-table 1.960 it meant that decentralization significantly affected to managerial performance. For variable of environment uncertainty (X2) t-Value is 5.561 > t-table 1.960, indicated that environment uncertainty significantly affected to managerial performance. For variable of accounting control (X3) t-Value is 7.207 > t-table is 1.960 it meant that the accounting control significantly affected to managerial performance